i-Syariah Check: a digital learning tool to enhance ethical understanding in Islamic finance education - Zaid, Muhammad Amirul Fahmi; Nazri, Muhammad Asyraf; Kardi, Nurul Asmiera; Misdi, Nuraliya Natasha; Kamis, Rohaiza (2025)
In response to the growing need for practical financial ethics education, especially in Islamic finance, i-Syariah Check is introduced as an interactive mobile application to support teaching and learning among students in Malaysia. This innovation serves as a digital learning tool that enables students to explore and evaluate the ethical compliance of Syariah-based financial products. By integrating real-world data, Fatwa rulings, and Syariah advisory input, the app allows users to simulate financial product assessments using ethical parameters such as the avoidance of riba (interest), gharar (uncertainty), and non-halal investments. In a classroom context, i-Syariah Check encourages critical thinking through case-based learning, promotes ethical awareness, and supports active student engagement in financial literacy topics. Educators can incorporate the app into lesson plans, group activities, or assessment tasks to bridge theory and real-life application of Syariah principles. This teaching innovation not only enhances students’ understanding of Islamic finance but also nurtures responsible decision-making in line with Syariah values. It aligns with the national education goal to strengthen applied knowledge and ethical competence in higher learning institutions.